IMPROVE-MENT NEWS. (Communications of the ACM, 2006)
The article announces that The Research Council of Norway has launched a new free electronic newsletter concerning software process improvement. The newsletter, which is called "Improve," will report and focus on developments related to methods and techniques of software process improvement. Among the topics that have been discussed are: agile software development, evidence-based software engineering, knowledge management, and effort management. The article provides information about the newsletter as well as the Research Council of Norway's Web site address.